Pancreatic Cancer Stem Cells: Their Role in Pancreatic Cancer Patient Outcomes and What Is Future? - Habib, Muzzamal; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
There is emerging evidence that stem cells might be playing an important role when it comes to cancer aggressiveness, metastasis, recurrence, resistance to chemotherapy and overall survival in hematologic malignancies as well as solid tumors including pancreatic adenocarcinoma. We review Abstract #e15058 presented at the 2013 ASCO Annual Meeting in Chicago by Andrikou et al.. Pancreatic cancer patients over-expressing pancreatic cancer stem cell markers were associated with aggressive tumors and worse survival. Image: Model of hierarchical organization of pancreatic cancer cell population.